The NR2B subunit and differential rearing: the role of the amygdala and hippocampus in the acquisition of Pavlovian conditioned fear - Reinhardt, Emily K. (Kansas State University, 2015)
Research has demonstrated that an enriched rearing environment improves learning in many tasks. However, growing evidence suggests that an enriched environment may not provide the same benefits during a fear conditioning paradigm. In fact, it appears that an isolated rearing environment may facilitate acquisition of fear to an aversive stimulus. The neural mechanisms responsible for this disparity in fear learning among differentially reared animals are currently unknown. The NR2B subunit of the NMDA receptor has been shown to be involved in the acquisition of fear and influenced by differential rearing, making it a prime candidate to begin investigating these underlying neural mechanisms. Therefore, this study assessed the expression of the NR2B subunit in brain regions important for the acquisition of fear (amygdala and hippocampus) among differentially reared rats. Rats were reared in an enriched, an isolated, or a standard condition for 30 days. They received four tone-footshock pairings, after which their brains were removed and expression of the NR2B subunit was quantified in the basolateral amygdala (BLA), central nucleus of the amygdala (ACe), and the CA3 region of the hippocampus. Analyses found that the isolated rats began to acquire fear to the aversive stimulus faster than the enriched and standard housed rats. However, the isolated rats showed the least amount of NR2B expression in the BLA while there were no rearing differences in expression within the ACe or the CA3. The results from this study provide further insight to the importance of the rearing environment in learning and memory, especially the learning of fear, and its central neural basis.
Keywords: Fear conditioning; Differential rearing; NR2B; Environmental enrichment; NMDA; Neurosciences (0317); Psychobiology (0349)